1998
DOI: 10.1111/j.1558-5646.1998.tb02016.x
|View full text |Cite
|
Sign up to set email alerts
|

RESOURCE ACQUISITION AND THE EVOLUTION OF STRESS RESISTANCE INDROSOPHILA MELANOGASTER

Abstract: Abstract.-Resistance to environmental stress is one of the most important forces molding the distribution and abundance of species. We investigated the evolution of desiccation stress resistance using 20 outbred Drosophila melanogaster populations directly selected in the laboratory for adult desiccation resistance (D), postponed senescence (0), and their respective controls (C and B). Both aging and desiccation selection increased desiccation resistance relative to their controls, creating a spectrum of desic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 41 publications
5
79
1
Order By: Relevance
“…Perhaps selection for increased survival in crude oil over shorter periods of time led to tradeoffs resulting in slower development. Such a tradeoff between survival and development time is concordant with studies that show increased development time in response to selection for stress tolerance, similar to what has been observed for evolutionary responses to low salinity (Lee et al., 2003, 2007), as well as to other forms of stress, such as starvation and desiccation stress (Barrera & Medialdea, 1996; Chippindale et al., 1998; Harshman, Hoffmann, & Clark, 1999). …”
Section: Discussionmentioning
confidence: 99%
“…Perhaps selection for increased survival in crude oil over shorter periods of time led to tradeoffs resulting in slower development. Such a tradeoff between survival and development time is concordant with studies that show increased development time in response to selection for stress tolerance, similar to what has been observed for evolutionary responses to low salinity (Lee et al., 2003, 2007), as well as to other forms of stress, such as starvation and desiccation stress (Barrera & Medialdea, 1996; Chippindale et al., 1998; Harshman, Hoffmann, & Clark, 1999). …”
Section: Discussionmentioning
confidence: 99%
“…Blows and HoVmann 1993). Thus, only one study has shown higher energy content due to accumulated carbohydrates ) while other studies diVer in energy content of metabolic reserves in desiccation-selected lines of D. melanogaster (Blows and HoVmann 1993;Chippindale et al 1998;Telonis-Scott et al 2006). In the present study, wild Xies of D. melanogaster have shown 2/3 of total energy due to carbohydrates in darker isofemale lines but from lipids in case of lighter Xies.…”
Section: Adult Xiesmentioning
confidence: 92%
“…However, in another study, energy content of D strains was 32% from carbohydrates but 68% from lipids while C strains obtained 14 and 86% from carbohydrates to lipids, respectively (cf. Chippindale et al 1998). Further, a new set of desiccation selected D and C strains of D. melanogaster showed equal (50%) energy content derived from carbohydrates to lipids (cf.…”
Section: Adult Xiesmentioning
confidence: 93%
See 1 more Smart Citation
“…There is an evidence of acquisition of greater carbohydrates as energy reserves to alleviate the consequences of desiccation stress in laboratory-selected desiccation-resistant strains of D. melanogaster (Graves et al 1992;Gibbs et al 1997;Chippindale et al 1998;Djawdan et al 1998). In contrast, large-sized insects (locusts and tse-tse flies), and a new set of laboratory-selected desiccation-resistant strains of D. melanogaster have shown storage of higher levels of lipid content under dehydration stress (Loveridge and Bursell 1975;Telonis-Scott et al 2006).…”
Section: Introductionmentioning
confidence: 91%